2011
DOI: 10.1016/j.bone.2011.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cobalt and chromium ions at clinically equivalent concentrations after metal-on-metal hip replacement on human osteoblasts and osteoclasts: Implications for skeletal health

Abstract: Metal-on-metal hip replacement (MOMHR) using large diameter bearings has become a popular alternative to conventional total hip arthroplasty, but is associated with elevated local tissue and circulating levels of chromium (Cr) and cobalt (Co) ions that may affect bone health. We examined the effects of acute and chronic exposure to these metals on human osteoblast and osteoclast formation and function over a clinically relevant concentration range previously reported in serum and within hip synovial fluid in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 34 publications
8
91
0
Order By: Relevance
“…In vivo data suggest that the concentrations of Co and Cr ions reported in serum and hip synovial fluid of patients with MoM implants have an effect on human osteoclasts. These ions have a mild stimulatory effect on developing osteoclasts, but have an inhibitory effect on mature osteoclasts at higher concentrations (equivalent to the levels found in synovial fluid) (65). The reason for this difference might be explained by the substrate resorbing activity of the cells and the dose-related toxicity of metal ions.…”
Section: Effects On Osteoclastsmentioning
confidence: 99%
“…In vivo data suggest that the concentrations of Co and Cr ions reported in serum and hip synovial fluid of patients with MoM implants have an effect on human osteoclasts. These ions have a mild stimulatory effect on developing osteoclasts, but have an inhibitory effect on mature osteoclasts at higher concentrations (equivalent to the levels found in synovial fluid) (65). The reason for this difference might be explained by the substrate resorbing activity of the cells and the dose-related toxicity of metal ions.…”
Section: Effects On Osteoclastsmentioning
confidence: 99%
“…A study evaluating the comparative cytotoxicity of cobalt, chromium, and cobalt-chromium alloy particles on MG-63 and SaOS-2 cells has shown that all three particle types inhibit alkaline phosphatase and osteocalcin expression, but cobalt particles inhibit these parameters to a much greater extent and are the only particles toxic enough to impair cell viability and type I collagen synthesis (Allen et al, 1997). Another study has shown that cobalt (Co 2+ , 0-10 ppm) and chromium (Cr 3+ , 0-150 ppm) ions generated from CoCl 2 and CrCl 3 are cytotoxic to MG-63 cells in a dose-and time-dependent manner over 72 hours, as (Andrews et al, 2011). All three ion types have reduced alkaline phosphatase production and mineralization, but only at doses > 100 M.…”
Section: Biological Response Of Osteoblastsmentioning
confidence: 99%
“…Working concentrations of each metal ion were prepared, as previously described 20. The stability of these metal ions in culture media has been confirmed previously using flame‐atomic absorption spectroscopy 20. Control treatment contained equivalent volume of sterile distilled water to maintain conditions, and referred to as 0 µg/L treatments.…”
Section: Methodsmentioning
confidence: 99%
“…Periprosthetic concentrations are several fold higher (median Co, 113 μg/L; median Cr, 54 μg/L),18 while patients with failing prosthesis have reported Co and Cr concentrations as high as 528 μg/L (range: 0–13,000 μg/L) and 1,844 μg/L (range: 0–38,600 μg/L), respectively 19. We recently demonstrated that exposure to Co 2+ and Cr 3+ adversely affects both osteoclast and osteoblast survival and function, including the mineralization of prosthesis surfaces in vitro, at concentrations equivalent to those found clinically 20, 21, 22…”
mentioning
confidence: 88%